Health risk analysis of Cd, Pb and Hg in blood mussel (anadara granosa) from Demak, Central Java, Indonesia - Bambang Yulianto (IOS Press BV, 2020)
The famous location of Wedung waters, Demak, Central Java, Indonesia, produces blood mussel, Anadara granosa. Anthropogenic activities can lead to contamination of heavy metals such as Pb, Cd and Hg to the living environment of A. granosa. This study was done to analyse heavy metals content in the soft tissue of A. granosa and health risks arising to Wedung residents from consuming the mussels. Heavy metals were analysed using atomic absorption spectrometry (AAS). The result showed that Cd and Pb contents were found in A. granosa soft tissue in the range of 0.56 - 0.70 mg/kg for Cd, 0.05 - 0.10 mg/kg for Pb and Hg was not detected. A health risk analysis showed that the HQ value for Pb from A. granosa intake was 0.0 <1, so that it was not at risk; whereas for Cd, the value reached 26.5 (HQ > 1). Thus, there was a noticeable health risk for the residents after consuming the mussel. The safety limit in consuming A. granosa was 0.33 g/day for children and 1.2 g/day for adults. Â© 2020 Lippincott Williams and Wilkins. All rights reserved.